A new species of Standleya (Rubiaceae, Coussareeae) with a new record for Bahia, Brazil - Jardim, Jomar Gomes; Costa, Cristina Bestetti (Phytotaxa, 2015)
Standleya glomerulata, a new species and a first record for the semiarid region of Bahia, Brazil, is described and illustrated. It differs from all other known species of the genus by its prostrate decumbent and reptant habit, glomerulate sessile inflorescences, and a calyx with two unequal lobes. S. prostrata has a similar habit, but can be distinguished by the pedunculate inflorescences and a calyx with four equal lobes. The new species is known from only a few localities in two protected areas and must therefore be considered threatened.